Implications of Evaporative Cooling by H2 for 1I/‘Oumuamua - Thiem Hoang; Abraham Loeb (The Astrophysical Journal Letters, 2023)
The first interstellar object observed in our solar system, 1I/‘Oumuamua, exhibited several peculiar properties, including extreme elongation and nongravitational acceleration. Bergner & Seligman (hereafter BS23) proposed that evaporation of trapped H _2 created by cosmic rays can explain the nongravitational acceleration. However, their modeling of the thermal structure of 1I/‘Oumuamua ignored the crucial cooling effect of evaporating H _2 . By taking into account the cooling by H _2 evaporation, we show that the surface temperature of H _2 -water ice is a factor of 9 lower than the case without evaporative cooling. As a result, the thermal speed of outgassing H _2 is decreased by a factor of 3. Our one-dimensional thermal modeling that takes into account evaporative cooling for two chosen values of thermal conductivity of κ = 0.01 and 0.1 WK ^−1 m ^−1 shows that the water ice volume available for H _2 sublimation at T > 30 K would be reduced by a factor of 9 and 5 compared to the results of BS23, not enabling enough hydrogen to propel 1I/‘Oumuamua.